Comparison of ethanol lock and heparin lock solution as prevention of catheter-related bloodstream infection in hemodialysis patients: systematic review and meta-analysis of randomized controlled trials - Amy Rosalie; Made Angga Putra; Muhammad Rizki Bachtiar; David Hermawan Christian; Ivan Joalsen (Journal of Indonesia Vascular Access, 2021)
Introduction: Catheter-related bloodstream infection (CRBSI) is a common complication of catheter use for vascular access in hemodialysis patients and a major cause of morbidity and mortality. Preventive measures, including antibiotic lock, are inadequate due to the risk of resistance and insufficient effect against bacterial biofilm. Ethanol, an antimicrobial substance, is a potential prophylactic lock-in preventing CRBSI. This study aims to assess ethanol lock's effectiveness in preventing CRBSI in hemodialysis patients with a catheter as vascular access and its impact on catheter dysfunction. Methods: Researchers systematically searched online databases including Pubmed, Cochrane Library, and Science Direct for relevant randomized controlled trials (RCTs) published within 2011 until 2020. Relevant data were pooled in PICOs (Population, Intervention, Control, Outcomes) format and analyzed with Review Manager (version 5.3.5, Cochrane Collaboration, Denmark). Results: Seven RCTs involving 453 patients were assessed. The primary outcome indicates that prophylactic ethanol lock significantly reduces the incidence of CRBSI compared to that of heparin lock (RR=0.32, 95% CI 0.12-0.83, p=0.02, heterogeneity I2=68%). The secondary outcome suggests no significant difference in the incidence of catheter dysfunction in ethanol lock and heparin lock (RR=0.75, 95% CI 0.23-2.40, p=0.63, heterogeneity I2=68%). Conclusion: Ethanol is a potential prophylactic lock agent in preventing CRBSI in hemodialysis patients with catheter access. Further research is needed to synchronize the procedural use of ethanol lock and evaluate its long-term effect.